Hay vida después de la muerte: la sucesión deportiva en el fútbol a la luz de FIFA y el TAS - Rosero Espinoza, Nicolás (2026)
This article examines the concept of "sporting succession", a legal mechanism developed within Sports Law, specifically in the context of disputes related to professional football industry. The first section outlines the legal framework applicable to football and traces the evolution of this figure in recent practice. The final section propose a harmonization of this doctrine with the Peruvian legal system, particularly in the context of sports-related insolvency.